The role of miR-199b-3p in regulating Nrf2 pathway by dihydromyricetin to alleviate septic acute kidney injury. (3rd July 2021) - Tian, Xiyan; Liu, Yufeng; Wang, Huaili; Zhang, Jianjiang; Xie, Lei; Huo, Yufeng; Ma, Wei; Li, Haiying; Chen, Xiaoxin; Shi, Peipei
Abstract: The pathophysiology of septic acute kidney injury (AKI) is very complex and the fatality is high. Nrf2 is crucial for septic AKI, and dihydromyricetin (DMY) has a protective effect on LPS-induced AKI. We aimed to explore whether DMY could affect Nrf2 pathway by regulating miR-199b-3p and played a protective role in septic AKI. The mouse model was induced by cecal ligation and puncture (CLP) and the cell model was stimulated by LPS. Enzyme-linked immunosorbent assay was conducted to examine MDA, SOD, LDH, GSH, TNF-α, kidney injury molecule 1 (KIM-1), and IL-6 levels. The pathological changes were observed by hematoxylin–eosin staining. The targeted relationship between miR-199b-3p and Nrf2 was verified by a dual-luciferase reporter assay. Levels of SOD, GSH, NQO-1, Nrf2, and HO-1 were decreased, MDA, LDH, TNF-α, IL-6, and KIM-1, and miR-199b-3p were increased in the CLP group and LPS-induced HK-2 cells, while the effect was reversed after DMY treatment. There existed renal tubule cell edema and necrosis, inflammatory cell infiltration in the CLP group, the situation was partially improved by DMY. MiR-199b-3p bound to Nrf2. Nrf2 levels were increased, TNF-α, IL-6, and KIM-1 were decreased after transfected with miR-199b-3p inhibitor, these effects were reversed when co-transfected with si-Nrf2. TNF-α, IL-6, KIM-1, and miR-199b-3p levels were increased; Nrf2, NQO-1, and HO-1 levels were decreased in the LPS + DMY + mimics-miR group. MiR-199b-3p was increased in septic AKI models, DMY might alleviate septic AKI by regulating miR-199b-3p to affect the Nrf2 pathway.